Tax Structure and Revenue Generation in Nigeria - Captain Briggs Alasin, Leyira Christian Micah (International Journal of Scientific Research and Management (IJSRM), 2017)
This study examines the relationship between tax structure and revenue generation in Nigeria from 1981 – 2016, time series data were collected from Central Bank of Nigeria (CBN) statistical Bulletin and publications of federal Inland Revenue service. Total federal collected revenue was modeled as the function of petroleum profit tax, company income tax, custom and exercise duty tax and value added tax. Multiple regressions with econometrics view statistical package were used as data analysis method. Co integration test, Augmented Dickey Fuller Test (ADF), granger Causality Test and vector error correction model we reused to estimation techniques were used to determine the dynamic relationship between the dependent and independent variables. R2 , Durbin Watson statistics, T-statistics, F-Statistics and β coefficient were used to determine and explain the extent to which the independent variables affect the dependent variable. The study found an R2 of 95.1%, adjusted R2 of 86.1% and F-statistics of 143.3082 with the probability of 0.000000.The β coefficient shows that petroleum profit tax have negative relationship while company income tax, custom and exercise duty tax and value added tax have positive relationship with total federal generated revenue. The negative relationship is attributed to fall in oil production and complexity in computing PPT which might lead to tax evasion. From the above, the study concludes that an equitable tax structure and a robust tax regime could enhance substantial revenue generation in Nigeria. It therefore recommends that policies that will enhance tax generation through effective tax structure should be formulated